Use of pharmaceuticals amongst athletes tested by Anti-Doping Norway in a five-year period - Gjelstad, Astrid; Herlofsen, Tine Marie; Bjerke, Anne-Linn; Lauritzen, Fredrik; Björnsdottir, Ingunn (Frontiers in Sports and Active Living, 2023)
Introduction The aim of the study was to map the use of pharmaceuticals by Norwegian athletes registered on doping control forms (DCFs) in a five-year period to examine general and some class specific use of pharmaceuticals across sports and athlete levels. Method Anonymous data from DCFs collected in 2015-2019 were manually entered into a database using the Anatomical Therapeutic Chemical (ATC) system for classification of the pharmaceuticals. Variables entered were year of control, gender, age group, athlete level, sport, test type, nationality, and pharmaceuticals (and dietary supplements) used. Results Pain killers in the ATC groups M01 A (Nonsteroidal anti-inflammatory drugs - NSAIDs) and N02 B (other analgesics), and anti-asthmatics in ATC groups R03 A and R03 B were the most frequently used pharmaceuticals. National level athletes reported more use of pharmaceuticals (1.4 ± 1.7 pharmaceuticals per form) than recreational level athletes (0.9 ± 1.2). The highest proportion of DCFs containing information about at least one pharmaceutical were found in speed skating (79.1%), alpine skiing (74.0%), rowing (72.4%) and cross-country skiing (71.7%). Painkillers were most frequently used in muscular endurance sports (30.4% and 21.2 % for M01A and N02 B, respectively) and ball and team sports (17.9% and 17.0%). Use of hypnotics was reported from ice-hockey players and alpine skiers in around 8% of the cases. Coclusion Use of anti-asthmatics was most often reported amongst athletes specially exposed to cold, chemicals and heavy endurance training. Athletes in specialized sports requiring high levels of strength and/or endurance reported a higher use of pharmaceuticals out-of-competition compared to in-competition, while there was no such difference in complex sports, such as team, gymnastic, aiming and combat sports.